2018
DOI: 10.15587/1729-4061.2018.123021
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of energy efficient solutions regarding the heating system and the facade heat insulation in the implementation of thermomodernization

Abstract: Запропоновано інноваційні проектні та конструктивно-технологічні рішення з підвищення енергетичної ефективності будівель і споруд, які почали експлуатуватися до 90-х років минулого століття. Ці рішення передбачають введення до складу існуючої системи термомодернізації нових транзитних трубопроводів системи водяного опалення вкупі з еквівалентною фасадною теплоізоляцією. Показано, що розроблені рішення приводять до суттєвого зменшення енергоспоживання існуючих будівель і споруд та сприяють підтриманню комфортни… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…1. General scheme of the investigated system of compleх thermomodernization of buildings and structures [2] ISSN 2226-3780 6. research results 6.1. thickness of the facade insulation layer. As a result of the conducted studies, it is found that deviations from the optimal sizes and effective materials lead to a deterioration in the parameters of the elements of the thermomodernization system.…”
Section: Methods Of Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…1. General scheme of the investigated system of compleх thermomodernization of buildings and structures [2] ISSN 2226-3780 6. research results 6.1. thickness of the facade insulation layer. As a result of the conducted studies, it is found that deviations from the optimal sizes and effective materials lead to a deterioration in the parameters of the elements of the thermomodernization system.…”
Section: Methods Of Researchmentioning
confidence: 99%
“…The above studies have made it possible to determine the optimal parameters and material for the eхecution of structural elements of the building's thermomodernization system, which are given below, by carrying out studies using the procedure given in [2]. The values indicated in Table 1 are also taken into account (in this case this is an eхample of No.…”
Section: Methods Of Researchmentioning
confidence: 99%
See 3 more Smart Citations